THE EFFECT OF CARBON DIOXIDE (C02) CONTENTNATURAL GAS ON THE PERFORMANCE CHARACTERISTICS OF A DIRECT INJECTION (DI) COMPRESSED NATURAL GAS (CNG) ENGINE - WASIU BABATUNDE, AYANDOTUN (2013)
The fast growing needs ofenergy in thetransportation sector have rejuvenated the drive for alternative fuels to fossil fuel for internal combustion engines with a view to whittling down the overdependence on fossil fuels, improving engine fuel economy and reducing exhaust emissions. Natural gas as an alternative fuel is mostly used due to its availability and adaptability to gasoline and diesel engines. Although, Malaysian is blessed with abundant natural gas reserves, the high carbon dioxide content (25- 89%) in the undeveloped natural gas reserves makes large scale utilization almost impossible. This study therefore examined the effect of high C02 content-natural gas on performance, combustion and exhaust emissions in a direct injection (DI) compressed natural gas (CNG) engine.